Landscape, Territory and Culture: Case study of the Siriri Flor de Atalaia dance group - Paula, Nátali de; Gulinelli, Érica Lemos; Benini, Sandra Medina (National Journal of City Management, 2024)
This article investigates the intersection between traditional cultural practices and the urban landscape, focusing on the cultural manifestations of Siriri and Cururu in the city of Cuiabá, Mato Grosso. The study highlights how these dance forms not only reflect but also shape the city's cultural and physical landscape, integrating in meaningful ways with urban life and local cultural heritage. The research specifically addresses the influence of these practices in public and free space, particularly in the courtyards used by the dance group Siriri Flor de Atalaia, which serve as vital stages for rehearsals and cultural presentations. The primary objective of this study is to analyze the transformations in the landscape of open spaces caused by the continuous interaction between the Siriri Flor de Atalaia group and its urban environment. This analysis seeks to understand how these spaces are used for the practice and dissemination of Siriri and Cururu culture, and how they contribute to the cultural dynamics of the city of Cuiabá. Through a detailed examination of physical and cultural changes in these places, the article explores the role of backyards and open spaces in perpetuating popular culture and forming a strong local identity. Methodologically, the study is based on a bibliographical review that addresses the themes of territory, open spaces, landscape and culture of the Siriri and Cururu dance. In addition, a case study of the courtyard of the dance group Siriri Flor de Atalaia is carried out, using direct observation and qualitative analyzes to capture the essence of cultural interactions and their impact on urban space. The results of the article provide an in-depth analysis of the cultural landscape formed around the Siriri Flor de Atalaia group, revealing how practice spaces not only serve as places for cultural activities, but also as elements that redefine the urban landscape. This investigation contributes significantly to debates about the importance of preserving and promoting cultural spaces within the urban environment, supporting the continuity of popular culture and informing public policies that value and promote traditional cultural practices in the city of Cuiabá. This study emphasizes the need for a more integrated and conscious approach to urban planning, which considers cultural practices as essential components of city development, not only for the preservation of heritage, but also as a vital strategy for enriching community life and strengthening local identity.
Keywords: Cuiabá; Popular culture; Cultural landscape